Assessing Knowledge and Attitude Regarding Drug Prescription among Dental House Officers- A Questionnaire-Based Study - Ayesha Ashraf, Hammad Hassan, Sarmad Fayyaz Farooqi, Salman Aziz, Ali Farooq, Irsam Haider (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the knowledge and attitude of dental house officers regarding proper drug prescription and factors influencing judgement of dental house officers during prescription writing. Methods: This descriptive cross-sectional study was conducted with the approval of review board of CMH Lahore Medical College. Online questionnaire with 17 close ended questions was developed the authors and distributed among 400 dental house officers working in various private dental institutes of Pakistan. Statistical analysis was carried out using IBM Statistical Package for Social Sciences version 25. Results: Majority of house officers relied on supervisor regarding drug prescription. Internet (37%), books (35.8%) as well as fellow colleagues (34.3%) was the other major sources of information. 8 out of 10 respondents ’always’ consider medical history before prescription writing. 14.8% responded that they always explain side effects to the patient. There was a significant difference between males and females when it comes to need of supervision. Majority of the females felt the need of supervision when it comes to prescription writing. Male house officers were more significantly influenced by senior colleagues/supervisor, fellow colleagues and pharmaceutical companies during drug prescription. Conclusion: The house offers should be instructed to explain side effects to the patients, take compete medical history and always consult with supervisor when confused. Workshops, refresher courses and constant supervision according to WHO Guide to Good Prescribing are essential to keep house officers up to date. Keywords: Dental, Drug prescription, History, House-officers, Medication, Prescription writing, World Health Organization